Determination of Fatty Acid Compositions of Some Raisin Cultivars in Turkey - Akin, Aydin (Asian Journal of Chemistry, 2010)
In this study, total fat content and fatty acid composition of 3 raisin cultivars grown in Konya in Turkey were determined by gas chromato-graphy. Polyunsaturated fatty acids (PUFA) were found to be higher than saturated fatty acid (SFA) and monounsaturated fatty acids (MUFA) in all samples. Palmitic acid was the major saturated fatty acid (15.84-24.23 % of total fatty acids) in all samples. Oleic acid was identified as the major monounsaturated fatty acids (9.72-16.01 % of total fatty acids) in all samples. Linoleic acid was the most abundant polyunsaturated fatty acids (47.80-60.74 % of total fatty acids) in all samples. It was shown that the fatty acid composition, w3/w6 fatty acids ratio and SFA/PUFA ratio between the raisin samples were varied.